The Relationship between Subclinical Hypothyroidism and Chronic Kidney Disease in Type Two Diabetes Mellitus in Al-Nasria City South of Iraq. - Kadhim Mohan Manhil Al-majedy (University of Thi-Qar Journal of Science, 2021)
The  association between subclinical hypothyroidism (SCH) and chronic kidney disease(CKD)in type2 diabetes mellitus is unclear. We examined whether SCH is associated with CKD in type2 diabetic patients in AL-Nasria city. Data  from 207 patients who visited  Al-Nasria diabetic clinic and Al-Hussain  teaching hospital  between  July 2013-october 2014 were  analyzed in cross-section study.    All patients with type2 diabetes mellitus were evaluated for glycaemic control, thyroid function and chronic kidney disease (CKD).CKD estimated by calculation of GFR from serum creatinine levels according to National Kidney Foundation.GFR levels were classified into five stages. CKD was define as eGFR 60 mL/min/1073 m2. The prevalence of SCH was 9.6%(n=20) among  patients with type2 diabetes mellitus. The SCH group had a higher prevalence of dyslipidemia (p=0.009)and CKD (decline in GFR) (p=0.034) than the euthyroid group. After adjustment  for potential risk factors of diabetes mellitus by multivariate logistic regression analysis, SCH remained significantly associated with CKD (odds ratio 2.086 (95% CI1.10-4.307, p=0.047),duration of diabetes(odds ratio 2.89 (95% CI 0.0-1.00 P=0.032),Dyslipidemia (odds ratio 4.849(95% CI 0.0-0.1.20  p=0.009). These results suggest that SCH was independently associated with CKD in type 2 diabetes mellitus.